The World Trade Center And Global Crisis : Some Critical Perspectives. - Kapferer, Bruce (Critical Interventions: A Forum for Social Analysis., 2013)
Numerous humanly caused destructions of just the last hundred years dwarf the World Trade Center disaster, and the attention still addressed to it may over the next few years appear disproportionate. But the significance of events is always determined by the social, political, and cultural forces that are articulated through a particular event. The attack of 9/11 was an event waiting to happen, and when it did occur the even itself became a catalyst and impetus for the changing and redirection of global realities. This volume offers provocative assessments of the reaction to the event from a.